2005
DOI: 10.1037/0021-843x.114.3.331
|View full text |Cite
|
Sign up to set email alerts
|

The Course of Depressive Symptoms in Men From Early Adolescence to Young Adulthood: Identifying Latent Trajectories and Early Predictors.

Abstract: Heterogeneity in the longitudinal course of depressive symptoms was studied using general growth mixture modeling for young men in the Oregon Youth Study (N = 206), from ages 15 to 24 years. Four trajectory classes were identified: the very low, the moderate-decreasing, the high-decreasing, and the high-persistent classes. The 3 lowest classes differed primarily quantitatively with the initial level or mean level across time being the major determinant of class differences, whereas the highpersistent class app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
157
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 140 publications
(185 citation statements)
references
References 49 publications
21
157
4
Order By: Relevance
“…Some other studies based on data-driven techniques identified family history of depressive symptomatology as a predictor for poor course trajectories. Stoolmiller et al (2005) found that parental depressive symptoms contributed to class discrimination, discriminating the high-persistent class from the other three classes. This finding was replicated by Olino et al (2010), who concluded that this pattern suggests that persistent depression may represent a more familial form of the disorder.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Some other studies based on data-driven techniques identified family history of depressive symptomatology as a predictor for poor course trajectories. Stoolmiller et al (2005) found that parental depressive symptoms contributed to class discrimination, discriminating the high-persistent class from the other three classes. This finding was replicated by Olino et al (2010), who concluded that this pattern suggests that persistent depression may represent a more familial form of the disorder.…”
Section: Discussionmentioning
confidence: 99%
“…A more extended follow-up would enable us to investigate the prevalence of Dysth in other course trajectories. Stoolmiller et al (2005) investigated lifetime depressive diagnoses in the identified classes. None in the very low group, 5.7 % in the moderate-decreasing group, 20.0 % in the high-decreasing group and 29.2 % in the highpersistent group were diagnosed with a lifetime depressive disorder.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations